Rhyolite lava dome growth styles at Chaitén volcano, Chile (2008-2009) : interpretation of thermal imagery - Bernstein, Marc (2015)
Airborne thermal images of the Chaitén rhyolite lava dome were obtained on three occasions between January 2009 and January 2010. These images were useful for understanding the nature and pace of growth of the newly extruded lava, which formed a complex of lobes and a spine. The images also revealed contrasting growth styles affecting different parts of the lava dome complex. Observed synchronous endogenous and exogenous growth was likely the result of multiple flow paths within the lava dome. We suggest that contrasts in morphology and surface texture between various lava lobes are the result of different extrusion rates.